The structural fate of lipid nanoparticles in the extracellular matrix - Bandara, Sarith R.; Molley, Thomas G.; Kim, Hojun; Bharath, Priyalini A.; Kilian, Kristopher A.; Leal, Cecilia (ROYAL SOC CHEMISTRY, 2020)
Drug-loaded liposomes are the most successful nanomedicine to date, with multiple FDA-approved systems for a myriad of diseases. While liposome circulation time in blood and retention in tissues have been studied in detail, the structural fate of liposomes-and nanoparticles in general-in the body has not been extensively investigated. Here, we explore the interactions of liposomes with synthetic and natural hydrogel materials to understand how the natural extracellular matrix influences liposome structural characteristics. Small angle X-ray scattering, confocal microscopy, and cryogenic transmission electron microscopy data demonstrate that poly(ethylene glycol) (PEG), gelatin, alginate, and Matrigel (R) hydrogels cause 200 nmliposomes of 1,2-dioleoyl-sn-glycero-3-phosphocholine (DOPC) to transform into micrometer-sized aggregates. These aggregates are composed of multilamellar vesicles around 100 nm in diameter with a mean interlamellar separation of 5.5 nm. Protecting the liposomes with a corona of PEG damps this restructuring effect, making the multilamellar vesicles less stable. We attribute this unilamellar to multilamellar transition to an osmotic driving force from the hydrogel environment. This lipid restructuring has broad ramifications in the design and use of nanomedicines, and in understanding the fate and function of natural lipid-based materials within the tissue microenvironment.
Keywords: GOLD NANOPARTICLES; RENAL CLEARANCE; PROTEINS; DNA; LIPOSOMES; MECHANISM; HYDROGELS; SYSTEMS; CELL